Role of Teledentistry in COVID-19 Pandemic: A Nationwide Comparative Analysis among Dental Professionals - Abbas, Beenish; Wajahat, Mehreen; Saleem, Zakia; Imran, Eisha; Sajjad, Mehvish; Khurshid, Zohaib (European Journal of Dentistry, 2020)
Objectives To assess knowledge, awareness, and practice of health care workers about the role of teledentistry in coronavirus disease 2019 (COVID-19).Materials and Methods A prevalidated structured questionnaire was used to evaluate awareness of general dentists, postgraduate dental students, dental educators, and consultants with postgraduation degrees toward teledentistry. The acceptability, reliability, and language clarity were also pretested. A total of 510 dental professionals contributed to this study.Statistical Analysis A statistical analysis using SPSS (version 20.0) was performed. Responses were noted as yes or no. A p-value of ≤ 0.05 was considered to be significant. Frequencies described data. Chi-square test was performed for intergroup comparison to evaluate if the knowledge and attitude diverge with the increase in the level of seniority in the profession.Results Awareness regarding teledentistry is high among general dentists with bachelor of dental surgery qualification in comparison to final-year students and postgraduate dental students. The majority of participants agreed with improvement in health care (88.20%), access to rural areas (82.90%), and general practicing dentist agreed with statistically significant difference (0.00) on saving time by teledentistry.Conclusion General practicing dentist was observed with high awareness of teledentistry as compared with postgraduate and undergraduate dental students.
Keywords: teledentistry; pandemic; COVID-19